THE ROLE OF PUPPET THEATRE IN THE ART OF COMEDY AND CLOWNING - Aliyeva Nazokat Shavkat qizi,A. Abduxalilov (International Journal of Literature and Language Studies, 2026)
The art of comedy and the art of clowning have served for centuries as a means of making people laugh, sharing positive emotions, and critically highlighting certain situations in social life. These art forms have been widespread among the people and have manifested themselves in various forms: from stage performances to street shows, from circuses to puppet theatre performances. In particular, puppet theatre occupies a special place in the development of this art. This article discusses the history of the development of the arts of comedy and clowning, the formation of puppet theatre in Central Asia, and its significance in these art forms.